Carcass quality traits and omega-3 content in different pork cuts from pigs fed a diet supplemented with linseed - Theeraphapsombut, K.; Sorapukdee, S.; Tangwatcharin, P. (International Journal of Agricultural Technology, 2022)
A total of 300 crossbred pigs were divided into three groups to evaluate the optimal slaughter weight for pig fed with linseed diet. The control pigs (C) were fed a commercial feed mixture with slaughter weight of 100-105 kg. The linseed fed pigs were fed a diet supplemented with 5% ground linseed during the growing-finishing periods and slaughtered with 100-105 kg (designed as low weight group, L) or with 110-115 kg (designed as height weight group, H). Four animals per groups were randomly selected for analysis of carcass quality traits, omega-3 (n-3) content, and lipid oxidation among different pork cuts. The results showed that feeding with linseed diet in H group seem to be higher Lenden-speck quotient (LSQ) index than L and C groups. There were no significant differences in lean cutting yields and percentage of retail cuts among treatments (P>0.05). Regarding n-3 contents, especially in form of alpha-linolenic acid (ALA, C18:3n3), ham, belly, boston butt, fore and hind legs, and backfat were higher in L and H groups than in control (P<0.05), which approximately 2.6−3.2 times greater than that in the control, depending on pork cuts. The oxidative stability of muscle lipids as indicated by TBARS values were not significantly differences among treatments (P>0.05). Due to the positive effects on higher n-3 content related to human health, linseed supplementation can be recommended in pig diet with commercial slaughter weight with 100-105 kg